STATUS AND PROBLEMS OF DEVELOPMENT OF CONSTITUTIONAL SCIENCE IN UKRAINE - V.M. Kampo (Економіка та право)
The article states that in the national dimension constitutional science is a collection or synthesis of interdisciplinary legal and other (economic, historical, political, philosophical, etc.) knowledge about the constitutional development of the country, the constitutional principles, values and institutions of power as means of management of state and social affairs on the basis and in accordance with the constitution, and so on. In essence, it is an encyclopedic science that covers a wide range of knowledge about the constitution, its legal, economic, ideological and other functions. Constitutional science differs from the science of constitutional law, although it is organically linked with the common object of research - the constitution and its significance in the legal maintenance of the functioning of the state and society. In practice, constitutional science analyzes, justifies, predicts and programs the constitutional development of society and the state. This development is due not only to legal phenomena, but also, first of all, to the processes of humanitarian development of society. Proceeding from the foregoing, in the development of constitutional science all other legal and humanitarian disciplines should be interested, as this will accelerate their constitutionalization. For example, this would bring the structure and values of the Constitution of Ukraine, in particular, the Criminal Code and other Ukrainian codes, etc., in line with the structure. Since some of the latter are still based today on the structural approaches and values of the Soviet era. The stages of modernization of constitutional science mentioned in the article are necessary in order to free the creative energy and intellectual potential of constitutionalists who are already able to solve the fundamental issues of the constitutional life of the country at a higher level than today. First of all, the question of the formation of a new, consistently democratic constitutional system, the protection of European common democratic values, the constitutional security of the state and the overcoming of the constitutional consequences of Russian aggression in the Donbas and the annexation of the Crimea.